The war and children in children's literature - Fernando Azevedo; Angela Balça; Moisés Selfa Sastre (Universidade Federal de Santa Catarina, 2017)
The texts of children's literature, proposing a modeling of realia, are excellent occasions to speak openly, about difficult subjects, seeking solutions to them. As always, difficult issues were somehow treated in children's literature, despite reservations society may or may not have in relation to its approach next to the young. Thus, our study focuses on three works of children's literature that discuss the war situation and allow to think and to question the place of the child in this context. The first work, in the format of a school notebook, is a tribute to children killed by the bombing of Gaza, carried out by Israeli forces in the summer of 2014. The second work speaks of a wall, a metaphor that separates people and worlds, and whose destruction is essential to ensure the achievement of a collective happiness. The third work sets up a witness: in the face of the misfortune of war and human misery, it´s important never give up and find strength to be reborn forever.Although the three works, united by a fictionality protocol, do not refer to the same historical and factual events, they can be read together, enhancing interpretations susceptible of helping children to think about the place that each one has and can play in a globalized society where the ideals of Peace, Brotherhood of Love and Respect for the Next still have to be heavily cultivated daily.